The master production schedule in MRP for microelectronic manufacturer - Cheam, Kai Wen; Mohd Nor, Norasmiha; Mohd Noh, Amieruddin Akhmarl; Awang Rosdi, Dayang Nur Qamarina; Roslan, Nor Azwany; Saibi, Noraikah; Saad, Shoib Ali Noor Aldeen (Penerbit UTHM, 2020)
Production planning and control coordinate the functions in accordance with a plan that economic use factory facilities and the movement of output is planned periodically (entire manufacturing cycle), from prepare all materials until the delivery of goods at planned time. Production is related to the conversion process involves step such as make decision on what to produce, the method to produce (how to produce), the estimated date to produce (when to produce), and more. To fulfill this task, our group chose CPU is one of the products in this microelectronics manufacturer. Organizing and plan the manufacture process generally occurs in production planning and control.